2014
DOI: 10.22319/rmcp.v5i2.3663
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento y calidad de forraje del pasto ovillo (Dactylis glomerata L.) al variar la frecuencia e intensidad de pastoreo

Abstract: El objetivo fue determinar el rendimiento y calidad del pasto ovillo (Dactylis glomerata L.), al variar la frecuencia e intensidad de pastoreo. Se evaluaron tres frecuencias (2, 3 y 4 semanas en primavera y verano y 4, 5 y 6 semanas durante otoño) y dos intensidades de pastoreo (severa: 3 a 5 cm y ligera: 6 a 8 cm de altura de forraje residual). Se evaluó el rendimiento de forraje, tasa de acumulación neta de forraje (TANF), composición morfológica y calidad del forraje. El mayor rendimiento acumulado y TANF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Grazing facilitates the physical breakdown, soil incorporation and rate of decomposition of residual plant material (Naeth et al, 1991). Villareal González et al (2014) evaluated orchard grass, and showed that yield was higher when it was intensively grazed (maintaining a remnant of 3–5 cm) than when it was grazed with light intensity (remnant of 6–8 cm). Our study yielded similar results since the simulated productivity of elongated wheatgrass was higher when a higher grazing intensity was applied (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Grazing facilitates the physical breakdown, soil incorporation and rate of decomposition of residual plant material (Naeth et al, 1991). Villareal González et al (2014) evaluated orchard grass, and showed that yield was higher when it was intensively grazed (maintaining a remnant of 3–5 cm) than when it was grazed with light intensity (remnant of 6–8 cm). Our study yielded similar results since the simulated productivity of elongated wheatgrass was higher when a higher grazing intensity was applied (Figure 6).…”
Section: Discussionmentioning
confidence: 99%